2011
DOI: 10.2147/ijn.s19013
|View full text |Cite
|
Sign up to set email alerts
|

Selective ex-vivo photothermal ablation of human pancreatic cancer with albumin functionalized multiwalled carbon nanotubes

Abstract: The process of laser-mediated ablation of cancer cells marked with biofunctionalized carbon nanotubes is frequently called “nanophotothermolysis”. We herein present a method of selective nanophotothermolisys of pancreatic cancer (PC) using multiwalled carbon nanotubes (MWCNTs) functionalized with human serum albumin (HSA). With the purpose of testing the therapeutic value of these nanobioconjugates, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In this study, the characterization of synthesized MGCNTs was performed using UV-visible spectroscopy, HRTEM, FTIR, and photoluminescence spectroscopy based on published methodologies 3638. Optical studies revealed that both MG and CNTs were present in the MGCNT conjugate as confirmed by the presence of absorption peaks for each in the conjugates 39,40. Successful conjugation of the dye to the CNTs was confirmed by the absorbance studies along with HRTEM, FTIR, and photoluminescence.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the characterization of synthesized MGCNTs was performed using UV-visible spectroscopy, HRTEM, FTIR, and photoluminescence spectroscopy based on published methodologies 3638. Optical studies revealed that both MG and CNTs were present in the MGCNT conjugate as confirmed by the presence of absorption peaks for each in the conjugates 39,40. Successful conjugation of the dye to the CNTs was confirmed by the absorbance studies along with HRTEM, FTIR, and photoluminescence.…”
Section: Discussionmentioning
confidence: 85%
“…A local increment of temperature can be obtained by exploiting different energy transduction approaches, such as the photothermal and the magnetothermal ones. Photothermal stimulation consists in the transduction of photon energy into heat and can be remotely triggered with NIR radiation in combination with many plasmonic nanomaterials, such as gold nanoshells (Erickson and Tunnell, 2010 ), gold nanorods (Huang et al, 2006 ), single-walled carbon nanotubes (Mocan et al, 2011 ), graphene oxide (Robinson et al, 2011 ), and copper sulfide (Cu 2 S) nanocrystals (Wang et al, 2015 ). Different independent works showed that photothermal stimulation is able to reversibly elicit a neural response in terms of spike activity, intracellular calcium levels, and neurite outgrowth (Yong et al, 2014 ; Paviolo and Stoddart, 2017 ).…”
Section: Remote Cell Stimulation Through Smart Nanomaterialsmentioning
confidence: 99%
“…Mocan T, et al 102 studied the PTA effects of PEGylated multi-walled carbon nanotubes on Panc-1 cells and the mechanism by which they induced cellular apoptosis. These authors also developed human albumin functionalized multi-walled carbon nanotubes (HAS-MWCNTs) that could induce selective photothermal ablation of pancreatic cancer under laser irradiation 104 . In that study, surgically resected specimens from patients with pancreatic cancer were preserved ex vivo and infused intra-arterially with HSA-MWCNTs via the greater pancreatic artery under ultrasound guidance.…”
Section: Photothermal Ablationmentioning
confidence: 99%